Changes in Near-Infrared Spectroscopy After Congenital Cyanotic Heart Surgery - Wong, Judith Ju-Ming; Chen, Ching Kit; Moorakonda, Rajesh Babu; Wijeweera, Olivia; Tan, Tracy Yi Shuen; Nakao, Masakazu; Allen, John Carson; Loh, Tsee Foong; Lee, Jan Hau (Frontiers in Pediatrics, 2018)
Background. Since oxygen saturation from pulse oximetry (SpO2) and partial pressure of arterial oxygen (PaO2) are observed to improve immediately after surgical correction of cyanotic congenital heart disease (CHD), we postulate that cerebral (CrO2) and somatic (SrO2) oximetry also improves immediately post-correction. We aim to prospectively examine CrO2 and SrO2, before, during and after surgical correction as well as on hospital discharge in children with cyanotic CHD to determine if and when these variables increase. Methods. This is a prospective observational trial. Eligibility criteria included children below 18 years of age with cyanotic CHD who required any cardiac surgical procedure. CrO2 and SrO2 measurements were summarized at six time-points for comparison: (1) pre-cardiopulmonary bypass (CPB); (2) during CPB; (3) post-CPB; (4) Day 1 in the pediatric intensive care unit (PICU); (5) Day 2 PICU; and (6) discharge. Categorical and continuous variables are presented as counts (percentages) and median (interquartile range), respectively. Results. Twenty-one patients were analyzed. 15 (71.4%) and 6 (28.6%) patients underwent corrective and palliative surgeries, respectively. In the corrective surgery group, SpO2 increased immediately post-CPB compared to pre-CPB [99% (98, 100) vs. 86% (79, 90); p<0.001] and remained in the normal range through to hospital discharge. Post-CPB CrO2 did not change from pre-CPB [72.8% (58.8, 79.0) vs. 72.1% (63.0, 78.3); p=0.761] and even decreased on hospital discharge [60.5% (53.6, 62.9) vs. 72.1% (63.0, 78.3); p=0.005]. Post-CPB SrO2 increased compared to pre-CPB [87.3% (77.2, 89.5) vs. 72.7% (65.6, 77.3); p=0.001] but progressively decreased during PICU stay to a value lower than baseline at hospital discharge [66.9% (57.3, 76.9) vs. 72.7% (65.6, 77.3); p=0.048]. Conclusions. CrO2 and SrO2 did not increase after corrective surgery of cyanotic CHD even up to hospital discharge. Future larger studies are required to validate these findings. (This study is registered with ClinicalTrials.gov ID: NCT02417259)